Should We Be Utilizing More Liver Grafts From Pediatric Donation After Circulatory Death Donors? A National Analysis of the SRTR from 2002 to 2017. Issue 9 (September 2021) - Sasaki, Kazunari; Nair, Amit; Firl, Daniel J.; McVey, John C.; El-Gazzaz, Galal; Diago Uso, Teresa; Fujiki, Masato; Aucejo, Federico N.; Quintini, Cristiano; Kwon, Choon-Hyuck D.; Hashimoto, Koji; Miller, Charles M.; et al.
Abstract : Background: Rates of withdrawal of life-sustaining treatment are higher among critically ill pediatric patients compared to adults. Therefore, livers from pediatric donation after circulatory death (pDCD) could improve graft organ shortage and waiting time for listed patients. As knowledge on the utilization of pDCD is limited, this study used US national registry data (2002–2017) to estimate the prognostic impact of pDCD in both adult and pediatric liver transplant (LT). Methods: In adult LT, the short-term (1-year) and long-term (overall) graft survival (GS) between pDCD and adult donation after circulatory death (aDCD) grafts was compared. In pediatric LT, the short- and long-term prognostic outcomes of pDCD were compared with other type of grafts (brain dead, split, and living donor). Results: Of 80 843 LTs in the study, 8967 (11.1%) were from pediatric donors. Among these, only 443 were pDCD, which were utilized mainly in adult recipients (91.9%). In adult recipients, short- and long-term GS did not differ significantly between pDCD and aDCD grafts (hazard ratio = 0.82 in short term and 0.73 in long term, both P > 0.05, respectively). Even "very young" (⩽12 y) pDCD grafts had similar GS to aDCD grafts, although the rate of graft loss from vascular complications was higher in the former (14.0% versus 3.6%, P < 0.01). In pediatric recipients, pDCD grafts showed similar GS with other graft types whereas waiting time for DCD livers was significantly shorter (36.5 d versus 53.0 d, P < 0.01). Conclusions: Given the comparable survival seen to aDCDs, this data show that there is still much scope to improve the utilization of pDCD liver grafts. Abstract : Supplemental Digital Content is available in the text.